Laparoscopic radical prostatectomy versus robot-assisted radical prostatectomy: comparison of oncological outcomes at a single center - Okegawa, Takatsugu (Prostate Int, 2020)
PURPOSE: The aim of the present study was to evaluate the pathological and oncological outcomes of laparoscopic radical prostatectomy (LRP) and robot-assisted radical prostatectomy (RARP) performed by one surgeon at a single center. SUBJECTS: We evaluated 700 patients with localized prostate cancer (i.e., 250 received LRP and 450 received RARP) in the study. The clinicopathological outcomes, positive surgical margin (PSM) frequency, and biochemical recurrence (BCR)–free survival were compared between LRP and RARP. RESULTS: At diagnosis, the median patient age and level of prostate-specific antigsen in the serum for LRP were 68 years and 8.1 ng/ml, respectively, while those for RARP were 66 years and 7.7 ng/ml, respectively. In the LRP group, the overall PSM rate was 31.2% (11.1% for pT2a, 19.0% for pT2b, 25.0% for pT2c, 60.0% for pT3a, 64.3% for pT3b, and 50% for pT4). In the RARP group, the overall PSM rate was 20.7% (4.8% for pT2a, 15.9% for pT2b, 12.9% for pT2c, 36.9% for pT3a, 46.2% for pT3b, and 100% for pT4). The PSM rate was significantly lower for RARP in men with pT2c, pT3a, or pT3b disease (p = 0.006, p = 0.009, and p = 0.027, respectively). Based on the multivariate analysis, RARP reduced the risk of BCR (hazard ratio = 0.8, p = 0.014). CONCLUSIONS: We compared the pathological findings and rates of BCR-free survival between patients who received LRP and those who received RARP at a single center. The rate of BCR-free survival was significantly higher in men classified as D'Amico high-risk patients who received RARP versus that reported in D'Amico high-risk patients who received LRP.